Pengaruh Lentur Balok Sloof Beton Bertulang Pada Struktur Kolam Renang Pada Apartement Mansyur Residence - Kartika Indah Sari; Yusrizal lubis; Juli Ratna Sari (Jurnal Simetri Rekayasa, 2021)
Reinforced concrete is a combination of concrete and steel reinforcement, which work together for the given load. Steel reinforcement will provide a strong tensile that is not owned by concrete. In the design of reinforced structures, the most important thing when doing the design is the loan that occurs due to the load that the structure is holding. Flexible concrete structures should be designed to have sufficient rigidity to limit borrowing that might weaken the strength or serviceability of the structure under working loads. The first step is analyzing reinforced concrete beams by calculating the external forces (Ultimate Moment) using the SAP2000 application with known materials from the data and working drawings, then comparing the results of the calculation of internal forces with the moment of resistance on materials with MuMn requirements. The calculation of the moment of resistance (Mn) is based on (SNI 2847: 2013). After calculating the Momentum and nominal limits, Mu = 9.0304 kN.m < Mn = 66,832 KN.m, so as to secure the construction of the concrete sloof against the loan.